The neuroendocrine immune network in ageing - Straub, Rainer H.; Mocchegiani, Eugenio (Neuroimmune biology, 2004)
The book describes the mechanisms involved in the maintenance of neuroendocrine-immune interactions in ageing. The lack of this maintenance leads to the appearance of age-related diseases (cancer, infections, dementia) and subsequent disability. The capacity of some hormones or nutritional factors in restoring and remodelling the neuroendocrine-immune response during ageing is reported presenting possible new anti-ageing strategies in order to reach healthy ageing and longevity.